Vancomycin-Nonsusceptible Enterococci Mediated by vanC at a Large Children’s Hospital: Prevalence, Susceptibility, and Impact on Care of Enterococcal Bacteremia - Dodson, Daniel S (Open Forum Infect Dis, 2020)
Enterococcus gallinarum and casseliflavus have inherent vancomycin resistance and, though known as pathogens, have not been well characterized in pediatric patients. We identified a significant prevalence of these enterococcal species among immunocompromised patients at a large pediatric institution and describe the impact on patient care, antibiotic stewardship, and infection control.